El maestro reflexivo, una postura abierta a la acción para el cambio - Jiménez Jaimes, Daniel (Educación y Ciudad, 2019)
The present article refers to the necessity of change and transformation to the convictions and beliefs that determine how the teacher feels about its professional labor. The problematics that affect its emotional and metal state, on how they are present form the entrance to the educational system and on how the teacher’s relations with the school environment validates some beliefs that affect its work performance. At the same time, a methodological proposal is presented based on the prepositive reflection, as an example of change from the personal experience of the teacher.